2013
DOI: 10.4103/0300-1652.122337
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of cervical cancer screening among market women in Zaria, Nigeria

Abstract: Background:Cervical cancer is the most common genital cancer and one of the leading causes of death among female population. Fortunately, this cancer is preventable by screening for premalignant lesions but this is rarely provided and hardly utilised. We assessed the knowledge, attitude and utilisation of cervical cancer screening among market women in Sabon Gari, Zaria.Materials and Methods:This was a cross-sectional study to evaluate the knowledge, attitude and practice of cervical cancer screening among mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
51
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 12 publications
15
51
4
Order By: Relevance
“…The lack of knowledge is mainly due to lack of population -based screening programs, inefficient mass media campaigns and cultural barriers wherein women in India feel shy to discuss the diseases affecting the sexual organs 20 . The majority of the women responded yes for smoking as a risk factor for cervical cancer which is similar to the report of Ahmed et al, 21 The knowledge of cervical cancer symptoms was poor among all age groups. Some of the very important symptoms of cervical cancer are vaginal bleeding after sexual intercourse and vaginal bleeding after menopause, very few of the subjects knew about these symptoms.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The lack of knowledge is mainly due to lack of population -based screening programs, inefficient mass media campaigns and cultural barriers wherein women in India feel shy to discuss the diseases affecting the sexual organs 20 . The majority of the women responded yes for smoking as a risk factor for cervical cancer which is similar to the report of Ahmed et al, 21 The knowledge of cervical cancer symptoms was poor among all age groups. Some of the very important symptoms of cervical cancer are vaginal bleeding after sexual intercourse and vaginal bleeding after menopause, very few of the subjects knew about these symptoms.…”
Section: Resultssupporting
confidence: 75%
“…Some of the very important symptoms of cervical cancer are vaginal bleeding after sexual intercourse and vaginal bleeding after menopause, very few of the subjects knew about these symptoms. The majority of the subjects were aware of the symptoms pelvic pain and postmenopausal bleeding which is similar to other reports by Ahmed et al, and Alok et al, 21,22 The women who have ever heard of cervical cancer were asked if they knew of any method that could prevent the disease. Among the total subject who could identify the major correct answer was 79.7% it is possible to prevent it, 82.1% early detection increase survival, 60.2% it is preventable but only 17.5% knew about vaccination against HPV.…”
Section: Resultssupporting
confidence: 51%
“…Other studies reported lower awareness of cervical cancer among female civil servant [29] and among market women in Nigeria [30,31]. Awareness of a disease condition often leads to reducing its morbidity and probably mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It can be readily detected in the premalignant phase, cervical cancer remains one of the most common cancer in Nigeria and fifth in the United Kingdom [1].…”
Section: Introductionmentioning
confidence: 99%